Pengaruh Disiplin Kerja Dan Pengawasan Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Pt Kereta Api Indonesia Persero Divisi L Regional Sumatera Utara - Nadia Ika Purnama; Rizka Amelia; Seprida Hanum Harahap (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
This study is an associative study with a quantitative method approach. The study population was employees of PT Kereta Api Indonesia Persero Division I North Sumatra Region with a total of 94 respondents. Data were collected through questionnaires and processed using SEM-PLS (Structural Equation Modeling - Partial Least Square). The results of the study indicate that work discipline has a positive and significant effect on employee performance while supervision does not have a significant effect on employee performance. Work discipline does not have a significant effect on job satisfaction, while supervision has a positive and significant effect on job satisfaction. Job satisfaction does not have a significant effect on employee performance. In addition, work discipline on employee performance through job satisfaction does not have a significant effect, and supervision on employee performance through job satisfaction also does not have a significant effect. The results of this study indicate that work discipline has a direct role in improving employee performance, while supervision has a greater effect on job satisfaction. However, job satisfaction does not function as a mediating variable in the influence of work discipline and supervision on employee performance.